2020
DOI: 10.32479/irmm.9714
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Mediating Role of Work Engagement Between the Relationship of Corporate Social Responsibility With Job Satisfaction and Organizational Citizenship Behavior

Abstract: This study investigates how perceived corporate social responsibility directly influence the job satisfaction and organizational citizenship behavior of employees, and indirectly influence through the mediating effect work engagement. A questionnaire-based survey was conducted to collect data from 327 students of MBA executive employed in different organizations of Lahore, Pakistan. Structural equation modeling was applied to test the hypothesized conceptual model. Results reveal that corporate social responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 74 publications
0
8
0
1
Order By: Relevance
“…Secondly, the current analysis results also showed that employees’ engagement could mediate CSR and employees’ advocacy behavior. Although the mediating potential of employees’ engagement as an antecedent of CSR was already established in the prior literature ( Chaudhary and Akhouri, 2018b ; Ali et al, 2020 ), its potential role to induce employees’ advocacy behavior was neglected. With this regard, the current study’s results showed that employees’ CSR perceptions about a socially responsible hotel help them induce their level of engagement, which then induces their advocacy behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, the current analysis results also showed that employees’ engagement could mediate CSR and employees’ advocacy behavior. Although the mediating potential of employees’ engagement as an antecedent of CSR was already established in the prior literature ( Chaudhary and Akhouri, 2018b ; Ali et al, 2020 ), its potential role to induce employees’ advocacy behavior was neglected. With this regard, the current study’s results showed that employees’ CSR perceptions about a socially responsible hotel help them induce their level of engagement, which then induces their advocacy behavior.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, different studies also reported that CSR is an enabler of employee engagement ( Duthler and Dhanesh, 2018 ). Specifically, in a plethora of studies, the mediating role of employee engagement, as an outcome of CSR, was reported ( Chaudhary and Akhouri, 2018b ; Ali et al, 2020 ). However, such mediating role of employee engagement between CSR and employees’ advocacy behavior was barely explored previously.…”
Section: Introductionmentioning
confidence: 99%
“…Các doanh nghiệp tham gia nhiều vào hoạt động trách nhiệm xã hội sẽ được nhân viên của họ đánh giá cao hơn đáng kể về những khía cạnh khác nhau trong công việc so với những doanh nghiệp ít tham gia trách nhiệm xã hội hơn (Tamm et al, 2010). Thực hiện trách nhiệm xã hội làm cho hình ảnh của công ty tốt hơn trong mắt nhân viên, điều này làm tăng cao SHL của nhân viên (Barakat et al, 2016;Story & Castanheira, 2019) và họ có thể tham gia vào các hành vi ngoài mô tả công việc chính thức của họ dưới hình thức giúp đỡ đồng nghiệp và tổ chức của họ đạt được mục tiêu cụ thể (Ali et al, 2020). Do đó, khi nhân viên nhận thấy rằng người sử dụng lao động của họ có trách nhiệm đối với xã hội, họ có xu hướng nhìn nhận tổ chức là một tổ chức hấp dẫn hơn để đồng hành (Zulfiqar et al, 2019) Số lượng quan sát được chọn thỏa mãn công thức theo nghiên cứu của Hair et al (2006), số lượng tối thiểu sẽ là: n=5*m (m là số lượng câu hỏi trong bài), như vậy với 37 câu hỏi trong nghiên cứu, áp dụng tỷ lệ 5:1, số lượng quan sát tối thiểu sẽ là: n=5*37=185.…”
Section: Mối Quan Hệ Giữa Shl Ltt Của Nhân Viên Và Trách Nhiệm Xã Hội...unclassified
“…The appointment of the new academic staff is one of the mechanisms used by the university in their recruitment process. The appointment allows fresh perspectives to be injected in the system while could help in contributing new ideas and implementation as well as able to foster positive attitude within the environment (Ali, A'tikah, Panatik & Zainal Badri, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Ali et al (2020) posited that it is crucial for the university to have such appointment to facilitate and share the aspiration in supporting the tertiary education agenda at the national level set by the Ministry of Higher Education (MOHE).…”
Section: Introductionmentioning
confidence: 99%